2021
DOI: 10.1177/15330338211019506
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Candidate Genes and Pathways in Basal/TNBC Patients by Integrated Analysis

Abstract: Purpose: This study aims to identify the key pathway and related genes and to further explore the potential molecular mechanisms of triple negative breast cancer (TNBC). Methods: The transcriptome data and clinical information of breast cancer patients were downloaded from the TCGA database, including 94 cases of paracancerous tissue, 225 cases of Basal like type, 151 cases of Her2 type, 318 cases of Luminal type A, 281 cases of Luminal type B, and 89 cases of Normal Like type. The differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…TNBC is a highly invasive malignant tumor, and its prognosis is worse than other subtypes of breast cancer. [ 15 ] Although TNBC is sensitive to chemotherapy, patients have limited benefit from it. [ 16 ] The main reason is that the tumor has strong drug resistance and obvious side effects of chemotherapy, and it is easy to relapse and metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…TNBC is a highly invasive malignant tumor, and its prognosis is worse than other subtypes of breast cancer. [ 15 ] Although TNBC is sensitive to chemotherapy, patients have limited benefit from it. [ 16 ] The main reason is that the tumor has strong drug resistance and obvious side effects of chemotherapy, and it is easy to relapse and metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA identified multiple candidate genes associated with BLBC and those genes were enriched in cornification, epidermis development, epithelial cell differentiation, estrogen signaling pathway, and pathways in cancer, which is consistent with the pathogenesis of BLBC. For example, the DEGs of triple negative breast cancer were also enriched in epidermis development according to the previous research [ 17 ]. In addition, some transcription factors essential for mammary luminal epithelial cell differentiation are also involved in the BLBC and estrogen receptor downstream target gene could inhibit the proliferation as well as migration of BC cells [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PXDNL and FOXD1 were reportedly involved in breast cancer pathogenesis and were significant in predicting prognosis. FOXD1 was found to be significantly related to the prognosis of basal-like breast cancer ( 32 ). Zhao et al ( 33 ) demonstrated that FOXD1 could increase cell proliferation and enhance chemoresistance of cancer cells by targeting p27.…”
Section: Discussionmentioning
confidence: 99%